Ethic of care and the competitive Ultimate Frisbee playing experiences of young women. Issue 3 (4th May 2017) - Spencer-Cavaliere, Nancy; Kingsley, Bethan C.; Gotwals, John K.
Abstract: Some young women's primary reasons for participating in sport (i.e. social interaction and friendship) may not match well with the structures embedded within traditional competitive sport (e.g. winning at all costs, aggression). In response, in this study, we explored if and in what ways these reasons align with an alternative sport – namely, Ultimate Frisbee. We examined how female adolescent players experienced, understood and engaged in Ultimate, in particular, with two unique aspects that help to define the sport's ethos: Spirit of the Game and self-officiating. Participants were nine female youth athletes who competed for Canada at a World Junior Championships. We used qualitative and interpretive description to examine data in the form of interviews, participant journals and reflective notes. Three themes captured the perspectives and playing experiences of the participants: (a) the Ultimate spirit, (b) the Ultimate sport and community and (c) the Ultimate player. Within these themes, the contextual nature of spirit of the game and players' sense of responsibility to uphold this ethos, the challenges of self-officiating and the significance of relationships with others in this sport community, were apparent. Ethic of care and previous literature on Ultimate were used to help interpret these findings. Ultimate, in a number of ways, aligned well with young women's reported reasons for taking part in sport. However, despite its claims as an alternative sport, it was still susceptible to the host of criticisms often associated with traditional competitive youth sport.